2020
DOI: 10.11609/jott.5746.12.8.15947-15950
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal observation of a Malayan Krait Bungarus candidus (Reptilia: Elapidae) feeding inside a building in Thailand

Abstract: Malayan Kraits Bungarus candidus have been reported to bite humans during the night after entering dwellings.  We report an observation of an adult krait feeding on a colubrid snake Chrysopelea ornata during the early morning, in the hallway of a large building at the center of a university campus in Nakhon Ratchasima, Thailand.  To our knowledge, this is the first observation of a wild B. candidus feeding within a building.  This observation provides insight into why kraits enter human settlements, and since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Malayan kraits ( B. candidus ) are highly venomous nocturnal elapids, ranging throughout Southeast Asia. B. candidus commonly occur in human‐modified habitats, such as agriculture, rural settlements and even suburban settlements, near forested areas (Chanhome, Cox, Vasaruchapong, Chaiyabutr, & Sitprija, 2011; Hodges, D'souza, & Jintapirom, 2020b; Knierim et al., 2018), where researchers have observed them entering occupied buildings in search of prey (Hodges et al., 2020b; Prasarnpun, Walsh, Awad, & Harris, 2005). In fact, many bite incidences occur while the victim is sleeping on the ground in rural settlements (Prasarnpun et al., 2005; Warrell, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Malayan kraits ( B. candidus ) are highly venomous nocturnal elapids, ranging throughout Southeast Asia. B. candidus commonly occur in human‐modified habitats, such as agriculture, rural settlements and even suburban settlements, near forested areas (Chanhome, Cox, Vasaruchapong, Chaiyabutr, & Sitprija, 2011; Hodges, D'souza, & Jintapirom, 2020b; Knierim et al., 2018), where researchers have observed them entering occupied buildings in search of prey (Hodges et al., 2020b; Prasarnpun, Walsh, Awad, & Harris, 2005). In fact, many bite incidences occur while the victim is sleeping on the ground in rural settlements (Prasarnpun et al., 2005; Warrell, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…We recorded two individuals feeding on snakes during the study; both were within anthropogenic land use types (fully reported in 37 , 65 ). The first occurred in a concrete gutter within 2 m of student housing.…”
Section: Resultsmentioning
confidence: 99%
“…We recorded two individuals feeding on snakes during the study; both were within anthropogenic land use types (fully reported elsewhere by Hodges, D’souza and Jintapirom, 2020; Hodges et al, 2021). The first occurred in a concrete gutter within 2 meters of student housing.…”
Section: Resultsmentioning
confidence: 99%